THE WALL-JET ELECTRODE POTENTIAL STEP CHRONOAMPEROMETRY - Fisher, A; Compton, R; Brett, C; Brett, A (1991)
A theory is presented which describes the transient current response to a potential step at a wall-jet electrode, thus defining the "response time" of the electrode. Results are given in the form of a normalized transient as a function of a dimensionless time parameter which permits the analysis of experimental data for electrodes of any geometry and for any solution flow rate. © 1992.